2015
DOI: 10.1093/nar/gkv299
|View full text |Cite
|
Sign up to set email alerts
|

Are mutagenic non D-loop direct repeat motifs in mitochondrial DNA under a negative selection pressure?

Abstract: Non D-loop direct repeats (DRs) in mitochondrial DNA (mtDNA) have been commonly implicated in the mutagenesis of mtDNA deletions associated with neuromuscular disease and ageing. Further, these DRs have been hypothesized to put a constraint on the lifespan of mammals and are under a negative selection pressure. Using a compendium of 294 mammalian mtDNA, we re-examined the relationship between species lifespan and the mutagenicity of such DRs. Contradicting the prevailing hypotheses, we found no significant evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 63 publications
3
9
1
Order By: Relevance
“…Interestingly, all previous works focused on major arc of mtDNA, but if authors take into account the whole mtDNA excluding D-loop (i.e. major and minor arcs together), the negative correlation disappeared [11]. Additionally, it has been shown that not only direct, but also inverted repeats negatively correlate with animal lifespan [3] probably by inducing mtDNA inversions and mitochondrial genome instability during mtDNA replication cycle [6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all previous works focused on major arc of mtDNA, but if authors take into account the whole mtDNA excluding D-loop (i.e. major and minor arcs together), the negative correlation disappeared [11]. Additionally, it has been shown that not only direct, but also inverted repeats negatively correlate with animal lifespan [3] probably by inducing mtDNA inversions and mitochondrial genome instability during mtDNA replication cycle [6].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of mtDNA deletion formation is of fundamental importance for understanding loss of mtDNA integrity and has been a subject of great interest and debate 12 . A commonly reported feature of mtDNA deletions is the presence of direct repeat (DR) sequences flanking the deletion breakpoints [13][14][15][16] . This observation has led to two major models of mtDNA deletion formation, namely the "slip-strand" model and the "double-strand break (DSB) repair error" model.…”
mentioning
confidence: 99%
“…Furthermore, it has been shown that the number of the inverted repeats in mitochondrial genome is correlated with mammalian longevity (J.-N. Yang, Seluanov, and Gorbunova 2013) . Recently, however, it has been shown that this correlation is not driven by negative selection against direct repeats in long -lived mammals (Lakshmanan et al 2015) , questioning the results of previous works.…”
Section: Introductionmentioning
confidence: 74%